An experimental study on the temperature dependency for horizontal shear performance of 300 × 300 square lead–rubber bridge bearing. (May 2015) - Chen, Y. Y.; Tan, P.; Liu, Bo.; Cui, J.; Ning, X. L.; Shen, C. Y.; Ma, Y. H.; Stiemer, S. F.; Zhou, F. L.
Abstract : It is widely accepted that the mechanical behaviour of lead–rubber bearing for bridge will change distinctly with temperature variation. This paper outlines an experimental study for 300 × 300 square type lead–rubber bridge bearing. The experimental results of temperature dependency for horizontal shear performance of lead–rubber bearing are presented. It can be seen that the horizontal shear stiffness of the bearing will be reduced as the temperature rises. The horizontal damping ratio of the bearing will be reduced as the temperature increases, but such a trend will not be obvious when the temperature is higher than 23°C. By using the classical regression analysis, estimation of the formula for temperature dependency for horizontal shear stiffness and horizontal damping ratio of 300 × 300 mm square lead–rubber bearings are given.